Incidence of anemia in pregnancy and its relationship with maternal characteristics and pregnancy outcome - Davaritanha F; Kaveh M; Salehi B (Tehran University of Medical Sciences, 2005)
Introduction: Anemia is a common finding among pregnant women, and it could cause a number of complications for both mother and fetus. Materials and Methods: In this case - control study, 302 pregnant women among patients referred to prenatal clinic of Mirza Kochak Khan Hospital were randomly chosen and were divided into anemic and normal groups based on their hemoglobin (Hb) level. Patients with Hb<11g/dl during the first or third trimester as well as those with Hb<10.5g/dl in the second trimester were considered anemic. Anemic patients were treated and pregnancy outcomes of two groups, including birth weight of the newborns, prematurity, stillbirth and abortion, were compared. Results: Overall prevalence of anemia during pregnancy was 8.6%. The prevalence of anemia in the first, second, and third trimesters of pregnancy were 10.3%, 3.5% and 12.7%, respectively. The frequency of anemia had a positive correlation with maternal age, gravidity and parity; however it was less frequent in patients taking iron supplements. There was no significant difference in pregnancy outcome of normal and treated anemic woman. Growth retardation was more frequent in treated anemic patients but only in women who were diagnosed in third trimester. Discussion: The prevalence of anemia among pregnant women is noticeable, and with the iron deficiency as the most common cause, we recommend administration of iron supplements for prevention of anemia and its maternal and fetal consequences. Treatment of anemia in early stages of pregnancy results in normal pregnancy outcome, a finding emphasizing the importance of treatment.